Wear Behavior of Brass Based Composite Reinforced with SiC and Produced by Stir Casting Process - E. Mohan; G. Anbuchezhiyan; R. Pugazhenthi; F. Peter Prakash (Materials Research, 2023)
Abstract The current investigation presents the wear-worn surface analysis of a silicon carbide-reinforced brass-based composite synthesized by stir casting. Wear behavior of the brass composite pin was analyzed by disc tribometer. Wear characterization studies and confirmation of elemental composition are investigated through scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) respectively. The worn surface of the synthesized brass composite was analyzed using atomic force microscopy (AFM). The aim of the investigation is to examine the surface morphology of the worn specimen. Based on the input constraints, the wear rate ranges from 0.0135 to 0.0893 mm3/min. The applied load is the predominant factor in the wear rate (83.75%). Sliding velocity has a minor effect on wear rate (1.06%). The improved surface roughness of 15.27 nm was produced on the worn surface. The novelty of the research work is to study the various surface parameters of the worn surface, such as roughness average, root mean square roughness, maximum height of the roughness, skewness, and kurtosis. These parameters were analyzed at different wear-worn surfaces of the synthesized brass composite. The wear-worn surface was deeply investigated and incorporated with SEM and AFM analysis.